2016
DOI: 10.2196/resprot.6580
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Usual Perioperative Care by eHealth to Enhance Postoperative Recovery in Patients Undergoing General Surgical or Gynecological Procedures: Study Protocol of a Randomized Controlled Trial

Abstract: BackgroundDue to the strong reduction in the length of hospital stays in the last decade, the period of in-hospital postoperative care is limited. After discharge from the hospital, guidance and monitoring on recovery and resumption of (work) activities are usually not provided. As a consequence, return to normal activities and work after surgery is hampered, leading to a lower quality of life and higher costs due to productivity loss and increased health care consumption.ObjectiveWith this study we aim to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…This process evaluation was carried out alongside a multicenter randomized clinical trial in seven teaching hospitals in the Netherlands (Netherlands Trial Registry NTR4699). A detailed description of the study design has been published earlier in this journal [ 10 ]. The study was reported in accordance with Consolidated Standards of Reporting Trials of Electronic and Mobile HEalth Applications and onLine TeleHealth (CONSORT-EHEALTH) [ 13 ] and was approved by the local medical ethics committee under the registration number 2014.301.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process evaluation was carried out alongside a multicenter randomized clinical trial in seven teaching hospitals in the Netherlands (Netherlands Trial Registry NTR4699). A detailed description of the study design has been published earlier in this journal [ 10 ]. The study was reported in accordance with Consolidated Standards of Reporting Trials of Electronic and Mobile HEalth Applications and onLine TeleHealth (CONSORT-EHEALTH) [ 13 ] and was approved by the local medical ethics committee under the registration number 2014.301.…”
Section: Methodsmentioning
confidence: 99%
“…A sample size calculation was performed; a total of 308 participants would be required. More details about the study population and sample size calculation have been described in the study protocol [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of e-health is very promising, allows for personalized 24-hour monitoring, and does not force postoperative problems onto the general practitioner or external emergency services. 6,14,27,31 The model we propose remains at an acceptable cost to our institution, which saves money by reducing the LOS. 8…”
Section: Implementation Of Erasmentioning
confidence: 99%
“…Patients undergoing these surgical procedures are chosen as part of the target population, next to those patients undergoing gynecological procedures including hysterectomy and adnexal surgery as the other part of the target population. This way, a broad patient population of general surgical and gynecological patients can be achieved [18][19][23][24]. The study population is divided in 1) the minor abdominal general surgical and gynecological procedures group which consists of laparoscopic cholecystectomy and adnexal surgery;…”
mentioning
confidence: 99%